A Conceptual Framework: The Effect of Digital Integration on Inventory Performance Through Supply Chain Visibility and Demand Forecast Accuracy in Indonesian FMCG Firms - Sadique Ali; Arry Widodo; R. Nurafni Rubiyanti (Best Journal of Administration and Management, 2026)
The Fast-Moving Consumer Goods (FMCG) industry in Indonesia has shown strong growth in recent years; however, firms still face ongoing supply chain challenges, such as high logistics costs, complex multi-tier distribution networks, and uneven levels of digital adoption. These issues highlight the importance of understanding how digital capabilities can effectively translate into improved operational performance. In response, this study proposes a conceptual framework that examines the impact of digital integration on inventory performance through the sequential mediating roles of supply chain visibility and demand forecast accuracy. Drawing on Information Processing Theory (IPT), digital integration is viewed as a key information-processing capability that helps firms manage uncertainty by improving data sharing, visibility, and decision-making across the supply chain. A quantitative, cross-sectional research design is proposed, with a target sample of at least 150 respondents from FMCG firms operating in Indonesia. Data will be collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The framework also includes control variables, such as firm size, firm age, and FMCG sub-sector, to capture differences across organizations. This study contributes to the existing literature by extending IPT into a multi-stage sequential mediation model, demonstrating how digital integration is translated into measurable performance outcomes through intermediate information-processing stages. It also offers practical insights for managers and policymakers by emphasizing that fully integrated digital ecosystems, rather than fragmented technological solutions, are essential for enhancing supply chain efficiency and inventory performance in emerging markets.